Perspektif Masyarakat Mandailing Perantau tentang Kesetaraan Gender - Rangkuti, Suheri Sahputra; Abidin, Zainal (Saree: Research in Gender Studies, 2022)
This article aims to find out how the views of the overseas Mandailing community regarding gender equality. The Mandailing ethnic community is one of the tribes that is well known for strictly adhering to the patrilineal system. The selection of the Mandailing people who have migrated is nothing but to see whether there has been a change in perceptions and the factors that have caused these changes and shifts. The research applied descriptive qualitative research methods with interview, observation, and documentation data collection techniques. This research resulted in the following findings: the perspective of gender equality among the Mandailing people who migrate has begun to be applied even though they do not understand the meaning of gender equality comprehensively; There has been a shift and change in perspective on gender equality among the Mandailing people who migrate to Medan City and its surroundings due to (1) the factor of Islam as the dominant religion embraced by the overseas Mandailing people; (2) the educational factor obtained by the overseas Mandailing community; (3) democratic factors that demand women's participation and participation. AbstrakArtikel ini bertujuan untuk mengetahui bagaimana pandangan masyarakat Mandailing di perantauan mengenai kesetaraan gender. Masyarakat etnis Mandailing merupakan salah satu suku yang terkenal sangat memegang teguh sistem patrilineal. Pemilihan masyarakat Mandailing yang telah merantau tidak lain adalah untuk melihat apakah telah terjadi perubahan persepsi dan faktor-faktor yang menyebabkan terjadinya perubahan dan pergeseran tersebut. Penelitian ini menggunakan metode penelitian kualitatif deskriptif dengan teknik pengumpulan data wawancara, observasi, dan dokumentasi. Penelitian ini menghasilkan temuan-temuan sebagai berikut: perspektif kesetaraan gender di kalangan masyarakat Mandailing yang merantau sudah mulai diterapkan meskipun belum memahami makna kesetaraan gender secara komprehensif; telah terjadi pergeseran dan perubahan cara pandang terhadap kesetaraan gender di kalangan masyarakat Mandailing yang merantau di Kota Medan dan sekitarnya disebabkan oleh (1) faktor agama Islam sebagai agama dominan yang dianut oleh masyarakat Mandailing di perantauan; (2) faktor pendidikan yang diperoleh masyarakat Mandailing di perantauan; (3) faktor demokrasi yang menuntut keikutsertaan dan partisipasi kaum perempuan.